2020
DOI: 10.1177/0305735620978688
|View full text |Cite
|
Sign up to set email alerts
|

Non-random acts of kindness: Joint music making increases preschoolers’ helping and sharing with an adult

Abstract: Research has shown that musical engagement promotes prosocial behavior in preschool-aged children under some conditions but not others. The current study tested whether an active musical interaction between a preschooler ( Mage: 56 months), an experimenter, and a research assistant would result in more sharing and helping behavior than a matched, non-musical interaction, while examining the extent to which a naturalistic musical interaction actually produced interpersonal movement synchrony. Verbal content was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…Conversely, the mean scores of children who did not enroll in group class showed a non-significant decreasing trend relative to their already lower starting point. These trends are consistent with previous research that has shown a link between cooperative music participation and empathy or prosocial behavior (Kirschner and Tomasello, 2010;Rabinowitch et al, 2013;Cirelli et al, 2014Cirelli et al, , 2016Good and Russo, 2016;Beck and Rieser, 2020). However, the lack of statistical significance in the present study leaves questions as to whether or not these trends might relate to Suzuki group music lesson participation specifically.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, the mean scores of children who did not enroll in group class showed a non-significant decreasing trend relative to their already lower starting point. These trends are consistent with previous research that has shown a link between cooperative music participation and empathy or prosocial behavior (Kirschner and Tomasello, 2010;Rabinowitch et al, 2013;Cirelli et al, 2014Cirelli et al, , 2016Good and Russo, 2016;Beck and Rieser, 2020). However, the lack of statistical significance in the present study leaves questions as to whether or not these trends might relate to Suzuki group music lesson participation specifically.…”
Section: Discussionsupporting
confidence: 90%
“…Music with a steady beat facilitates interpersonal synchronization, and infants whose movements synchronize with another person while listening to music are subsequently more likely to help that person (Cirelli et al, 2014) and also more likely to help a third party who poses as a 'friend' of that person (Cirelli et al, 2016). Children who engage in musical play together show more spontaneous helping behavior and cooperation (Kirschner and Tomasello, 2010), and musical play between preschoolers and adults has been shown to result in significantly more interpersonal synchrony and spontaneous helping behavior, regardless of the verbal content of the music (Beck and Rieser, 2020).…”
Section: Music Empathy and Prosocial Behaviormentioning
confidence: 99%
“…Kirschner and Tomasello (2010), for example, found that 4-year-olds who engaged in musical play cooperated more with peers than same-aged children, who only played together in the absence of music. Beck and Rieser (2020) found similar results. Preschoolers (aged 3–5 years) in their study displayed more helping behaviors toward the researcher after engaging in a musical play.…”
Section: Musical Activities and Prosocial Behaviorssupporting
confidence: 62%
“…For example, Schellenberg et al (2015) showed that music training in a group facilitates the development of prosocial skills. Also Beck and Rieser (2020) provided evidence that music making may facilitate prosocial behavior in preschoolers. Furthermore, joint active music making fosters connection and close relationships, not only within the smaller community (e.g., family), but also in the broader community and even with strangers.…”
Section: Music and Resiliencementioning
confidence: 99%